The most important thing illuminated : uncommon sense for the thoughtful investor - Marks, Howard, 1946- (Columbia Business School Publishing, 2012)
In May of 2011, Columbia Business School Publishing released Howard Marks' The Most Important Thing, a book that distilled the wisdom of Marks' celebrated client memos into a single volume, making his time-tested investing philosophy available to general readers for the first time. The book was greeted with wide acclaim from investors--professional, casual, aspiring, and armchair alike--and became a business bestseller. Now, Columbia Business School Publishing is proud to announce an innovative digital edition that allows you to read Marks' words alongside comments, insights and counterpoints from four other renowned investors and investment educators: Christopher Davis, Joel Greenblatt, Paul Johnson and Seth Klarman. See what these investors think of such concepts as "second-level thinking," the price/value relationship, patient opportunism, and defensive investing. There are also annotations from Howard Marks himself, highlighting some of the themes that ...